Students’ scientific reasoning skills through RICOSRE model in environmental changes topic - H. Hasruddin; Ratu Nurul Aulia (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The low level of students' scientific reasoning skills is caused by the low-quality learning process. Action is needed to improve the learning process by applying innovative learning models, the Reading, Identification, Constructing, Solving, Reviewing, and Extending (RICOSRE) learning model. This research aims to determine the effect of RICOSRE Learning Model on Students' Scientific Reasoning Skills on the Topic of Environmental Changes of Class X MAN 1 Medan. This research uses a quasi-experiment with Non-equivalent Control Group Design. The population of this study is all class X Science and Technology MAN 1 Medan. The sample consisted of class X Science and Technology 1 with the RICOSRE learning model and X Science and Technology 2 with the conventional learning model. The results of the research show that the average pre-test and post-test data for scientific reasoning skills in the experimental class are 35.65 and 79.14, moreover in the control group are 33.94 and 67.76. Data was analyzed using an Independent Sample t-test using SPSS Version 26. Based on the t-test calculation at α = 0.05, a significance of 0.000 is obtained, which means there is an effect of the RICOSRE model on the scientific reasoning skills of students on environmental change topics.